A Systematic Review: Post Quantum Cryptography to Secure Data Transmission - Hussein, Asma Ibrahim; MaoLood, Abeer Tariq; Gbash, Ekhlas Khalaf (Iraqi Journal of Science, 2024)
A significant topic of contemporary cryptography research and standardization is the development of public key crypto systems that resist attacks from quantum computers. Protocols and applications should start investigating the use of quantum-resistant key exchange and encryption to protect the confidentiality of current communications against future quantum computers utilizing post-quantum cryptography for a particular key exchange. Since they operate harder and need fewer steps compared to conventional computers, quantum algorithms are more secure and robust. Attackers who use quantum computers have powerful computing capabilities, and a quantum allows for simple cryptographic system breaking. Security algorithms that are quantum secure are resistant to attacks from conventional, as well as quantum computers. This work has surveyed, summarized, and analysed previous research to provide readers of this study an integrated understanding of quantum cryptography. It also discusses quantum attacks, which could be used in place of more conventional cryptography techniques, such as quantum key distribution, which takes advantage of quantum mechanics' properties to ensure secure exchanges of the secret keys, and various quantum algorithms. With quantum computation becoming a very real threat, this should motivate more people to show an early interest in the future of cryptography.